Reactivity as a characteristic of temperament in relation to tolerance of dental treatment stress - Terelak, Jan Felicjan; Jolanta, Rosińska; Jasiński, Tadeusz; Turek, Mariusz; Margańska, Małgorzata (Studia Psychologica: Theoria et praxis, 2002)
The work is empirical in character and concerns findings in the relationship between temperament and susceptibility to dental treatment stress in actual conditions of dental operations. It was founded that tolerance of dental treatment stress is linked to specific temperamental structure, i.e. low reactivity, low emotional excitability and low level of fear as characteristics. Strelau’s Temperament Questionnaire, Spielberger’s STAI and Eysenck’s MPI were applied and heart rate monitored. In accordance with the established hypothesis, the existence of influence of reactivity as a characteristic of temperament on the level of dental treatment stress was confirmed, namely, in persons of high reactivity compared with those of low reactivity. High level of fear in the course of the whole dental experiment as well as higher dynamic of change in this indicator was also confirmed. The extent of relationship with regard to the second indicator of dental treatment stress, namely the physiological indicator (heart rate) as not confirmed.